CORPORATE IMAGE AND TRUST ON PATIENT LOYALTY: STUDY OF SOUTHEAST SULAWESI REGIONAL POLICE PRATAMA CLINIC PATIENTS - Ratnawati, Lisdia; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT The health sector is the primary service sector in various countries as it plays a vital role in maintaining and improving public health to achieve a nation's goals. Currently, the healthcare service industry is one of the promising business opportunities due to high competition and rapid growth. Health issues have become an essential need for society. Health is considered invaluable and costly, leading everyone to aspire to live a healthy life. This study aims to examine the influence of corporate image and trust on patient loyalty at the Pratama Clinic of the Southeast Sulawesi Regional Police. The research adopts a quantitative approach involving 120 respondents. Primary data is utilized as the information source, and the analysis is conducted using the Structural Equation Modeling (SEM) AMOS method. The research results indicate that positive corporate image and trust have a significant impact on patient loyalty. This finding suggests that a positive perception of the corporate image and a high level of trust from patients towards the clinic contribute to their loyalty. Therefore, maintaining and enhancing the corporate image, as well as building positive trust, are crucial strategies for retaining and improving patient loyalty. This study also provides theoretical and practical implications and can serve as a reference for future research. Keywords: Corporate Image, Trust, Patient Loyalty